A comprehensive review of digital twin applications in electric vehicles: Evolution, classification, and future directions towards Industry 5.0 - Arun Jose; Sonam Shrivastava (Results in Engineering)
Digital twins have played a vital role in the digitization of manufacturing processes by completely transforming the industry's approach to optimization, design, maintenance, safety, decision-making, and remote access and training methods. Despite growing interest, the literature that covers the evolution, classification, and integration of digital twins with Industry 5.0 is not comprehensive. Many studies either focused on specific technical aspects or did not provide a thorough overview of recent technological advancements, integrated frameworks, or other potential areas for future research. This review offers an in-depth examination of how digital twin technology is applied in the electric vehicle sector, particularly focusing on its role in managing electric vehicle batteries. This study introduced a structure resembling an inverted pyramid divided into five sections. Through a comprehensive bibliometric analysis of various databases, relevant literature on this topic was identified, resulting in the discovery and examination of 328 potential papers. This groundbreaking study offers a comprehensive overview of the development of digital twin technology since its inception in 2003. It explores general classifications and applications, followed by an in-depth examination of digital twin usage in the automotive industry, with a particular focus on electric vehicles and their battery management systems. A thorough critique of recent literature and an investigation into the reproducibility of these studies were presented, offering valuable insights for practitioners, researchers, and industry professionals to conceptualize the application of digital twins.